2006
DOI: 10.1364/oe.14.001878
|View full text |Cite
|
Sign up to set email alerts
|

Endoscope-tip interferometer for ultrahigh resolution frequency domain optical coherence tomography in mouse colon

Abstract: Frequency domain optical coherence tomography (FD-OCT) allows interferometer topologies with simplified system construction and handling. Problems of dispersion and polarization matching between the sample and reference arms, as well as beamsplitter spectral non-uniformity, are mitigated when the interferometer is wholly contained in the endoscope tip. A common path set-up, using a reference reflection originating from the inside surface of the glass envelope at the distal end of the endoscope, and an alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
62
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 31 publications
1
62
0
Order By: Relevance
“…As a result, there has been great interest in improving the resolution of OCT by an order of magnitude along each dimension to enable visualization of abnormal cells in living patients [4]. Near-isotropic μm-resolution forms of OCT have been termed ultra-high-resolution OCT (UHR-OCT) or μOCT in literatures [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, there has been great interest in improving the resolution of OCT by an order of magnitude along each dimension to enable visualization of abnormal cells in living patients [4]. Near-isotropic μm-resolution forms of OCT have been termed ultra-high-resolution OCT (UHR-OCT) or μOCT in literatures [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Combining these two complementary imaging technologies would potentially improve the diagnostic capability for early cancer detection. Previous studies using OCT and depth-integrated fluorescence imaging already showed substantial promises in cervical [30,31], bladder [29,32], colorectal [33][34][35], and bronchial cancers [36]. However, depth-integrated fluorescence imaging lacks the depth-resolved information, therefore may not sufficiently indicate the subsurface lesions or estimate the depth-extent of the lesions.…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach compromises co-registration of the two modalities. Other reported approaches have used single Ti-Sapphire broadband femtosecond (fs) laser sources for both spectral domain OCT and multiphoton excited fluorescence imaging systems [25][26][27][28][29][30][31][32]. Double-clad fiber (DCF) can also provide a common path for the two modalities that ensures co-registration.…”
Section: Introductionmentioning
confidence: 99%